2015
DOI: 10.1097/jcp.0000000000000389
|View full text |Cite
|
Sign up to set email alerts
|

Remission Rate and Functional Outcomes During a 6-Month Treatment With Osmotic-Release Oral-System Methylphenidate in Children With Attention-Deficit/Hyperactivity Disorder

Abstract: Many definitions have been used to evaluate remission in patients with attention-deficit/hyperactivity disorder (ADHD) in different studies resulting with varied remission rates. This open-label, multicenter study investigated the remission rate in Chinese children (n = 239; aged 6-16 years) with a diagnosis of ADHD (Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition), treated with osmotic-release oral-system methylphenidate at doses of 18, 36, and 54 mg, once daily. Two definitions of remis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
(55 reference statements)
1
12
0
Order By: Relevance
“…Published response rates for OROS-MPH based on this criterion (62% and 66%) are within the range of response rates found in the present analyses (Biederman et al, 2006(Biederman et al, , 2010. Likewise, published values for the proportions of OROS-MPH-treated participants who achieved symptom remission based on SNAP-IV scores (69.3% and 73.2%) are similar to the proportions of participants in the present analyses who achieved an ADHD-RS-IV total score of ⩽18 at the end point (Su et al, 2015). With regard to ATX treatment, the proportion of participants achieving at least a 30% reduction in ADHD-RS-IV total score plus a CGI-I score of 1 or 2 in the present analyses was similar to the 60% who achieved a 25% reduction in ADHD-RS-IV total score in a large retrospective study (1069 patients) that investigated predictive factors for response to ATX (Newcorn et al, 2009).…”
Section: Trialsupporting
confidence: 86%
“…Published response rates for OROS-MPH based on this criterion (62% and 66%) are within the range of response rates found in the present analyses (Biederman et al, 2006(Biederman et al, , 2010. Likewise, published values for the proportions of OROS-MPH-treated participants who achieved symptom remission based on SNAP-IV scores (69.3% and 73.2%) are similar to the proportions of participants in the present analyses who achieved an ADHD-RS-IV total score of ⩽18 at the end point (Su et al, 2015). With regard to ATX treatment, the proportion of participants achieving at least a 30% reduction in ADHD-RS-IV total score plus a CGI-I score of 1 or 2 in the present analyses was similar to the 60% who achieved a 25% reduction in ADHD-RS-IV total score in a large retrospective study (1069 patients) that investigated predictive factors for response to ATX (Newcorn et al, 2009).…”
Section: Trialsupporting
confidence: 86%
“…Seven of the 17 non-randomized studies were prospective cohort studies ( 60 , 63 , 65 - 67 , 71 , 72 , 74 , 75 ). Three studies were randomized clinical trials without placebo or no-intervention comparators and therefore assessed as prospective cohort studies by only including the methylphenidate groups ( 58 , 59 , 70 ).…”
Section: Resultsmentioning
confidence: 99%
“…All studies were carried out in outpatient clinics, except one study, which only included hospitalized patients (64). Comorbid schizophrenia, psychotic disorder or psychiatric disorder were exclusion criteria in twothirds of the studies (58)(59)(60)63,65,66,70,71,(73)(74)(75). Five studies only included patients with comorbid disorders, including schizophrenia (64), comorbid conduct disorder or oppositional-defiant disorder (59), severe mood dysregulation (60), sleeping difficulties (58) and velocardiofacial syndrome (49).…”
Section: Non-randomized Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One investigation specifically attempted to validate the criteria for ADHD remission against actual functional outcomes, and found that patients who achieved remission via two differing definitions based on an ADHD symptom severity had significantly greater functional improvement at 8 and 24 weeks of follow-up than non-remitters. 10 While these findings are reassuring in demonstrating that treatment of symptoms has downstream impact on functioning and well-being, they also illustrate that optimisation of functional improvement can only be achieved if we measure and identify those areas of impairment that are problematic. Examples might include life skills that require organisation skills training, deficits in self-esteem that indicate the need for psychotherapy, or family conflict that would benefit from parent training or family therapy.…”
Section: Understanding Functional Impairmentmentioning
confidence: 91%